Guidelines For The Development Of Academic Competencies In The New Normal For Lecturer Of Rajabhat University, Thailand - et. al., Sirivadee Wiwithkhunakorn, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Competency refers to the ability of a person to express himself to perform the duties for which he is responsible. University lecturers play four important roles: teaching and learning, research, academic service, and art and culture preservation. Rajabhat University is considered to be among the universities for the development of local communities according to their service area. However, if the personnel of Rajabhat University have high performance, it will be beneficial to completely drive the mission of the university. The objective of this research is to study the guidelines for the development of academic competency of Rajabhat University lecturers. Research sources providing key information including experts, academics, and experts, totaling 10 people. The tools used for collecting were questionnaires and interview records. The data analysis using systematic analysis. The results of the research were as follows: Guidelines for academic competency development of Rajabhat University lecturers are as follows: (1) Principles of academic competency promotion development are as follows: Finding the need for development, strategic planning of development, driving development projects, monitoring, and evaluation of human resource development projects. (2) The guidelines for competency development include self-development, training and study visits, higher education, strategic management, operational processes. Performance evaluation. (3) Urgent development policy, including Establishing human resource development plans, managing operational barriers, and Driving human resource development.